Ciguatoxin â€“ an Emerging Biological Hazard among Reef Fishes of India - Rajisha, R.; Kishore, Pankaj; Panda, S. K.; Ashok Kumar, K. (Fishery Technology, 2018)
Ciguatera Fish Poisoning (CFP) is an emerging foodsafety hazard which has been reported in southernpeninsular India in recent times. Ciguateric fishesmostly associated with coral reef ecosystem areimplicated in food poisoning outbreaks. USFDAguidance for fish and fishery products classifies CFPas â€œreasonably likely to occurâ€ in fishes harvestedfrom coral reef regions. Ciguatera Fish Poisoninghas been reported from tropical or subtropical areasaround the world between latitudes 35Â°N and 35Â°S,particularly in the Caribbean, Pacific and IndianOcean and in the Flower Garden Banks area in thenorthern Gulf of Mexico. Action levels for CFPlimits are now listed as 0.01 ppb for Pacific and0.1 ppb for Caribbean ciguatoxin. CFP is consideredas a natural toxin and USFDA has listed out 12group of fishes under ciguatera hazard category.With recent EU import rejections of some of theseafood consignments originated from India, CFPhas emerged as an important food safety concern.Although, no fatality has been reported so far,morbidity symptoms observed from cases of hospitalizationis a definite concern to the export trade.This review deliberates on the significance of CFP,its distribution and hazard control measures.